POLICIES AND STRATEGIES FOR THE IMPLEMENTATION OF YOGYAKARTA CITY FOOD SECURITY - Syarief Aryfaid; Widodo R. Triputro (Jurnal Ekonomi, 2022)
There are three main components in food security, namely, food availability, food access and food utilization (staple ingredients). processed which is intended as food or drink for human consumption, including food ingredients, food raw materials, other materials used in the process of preparing, processing, and/or making food or beverages. where researchers conducted an analysis of various food security policies organized by the Yogyakarta City Government. The problems faced by the government of the City of Yogyakarta, the limited availability of agricultural land, the increase in the population of Yogyakarta is increasing sharply, the need for food is increasing, the reduction of agricultural land that is converted into residential and industrial land, is a threat and a challenge to realize food security. This study focuses on various policies carried out by the Yogyakarta City Government in organizing and ensuring food security in the city of Yogyakarta. This study aims to describe, analyze, and explain carefully various programs, activities, and concrete steps of the Yogyakarta City Government related to food issues and to find out the obstacles faced by the Yogyakarta City Government in implementing food policies, food security and handling food affairs in order to meet the availability of food. quality and affordable food for the people of Yogyakarta City. The research method used is descriptive qualitative with a narrative approach, the data collection methods are field observations, surveys, interviews, focus group discussions, documentation and document collection. The results of the study indicate the food security policy formulated by the Yogyakarta City Government, namely optimizing existing agricultural land and protecting the conversion of productive agricultural land, as well as carrying out various programs and activities oriented to the stability of the supply of good quality food for the needs of the community. However, the policies formulated by the Yogyakarta City Government are not yet strategic and long-term, because they have not optimized direct cooperation with regions that have agricultural land bases.